German Jews in the era of the "final solution" : essays on Jewish and universal history - Ḳulḳah, Oṭo Dov 1933-2021 (De Gruyter Oldenbourg, 2020)
These essays, written in the course of half a century of research and thought on German and Jewish history, deal with the uniqueness of a phenomenon in its historical and philosophical context. Applying the "classical" empirical tools to this unprecedented historical chapter, Kulka strives to incorporate it into the continuum of Jewish and universal history. At the same time he endeavors to fathom the meaning of the ideologically motivated mass murder and incalculable suffering. The author presents a multifaceted, integrative history, encompassing the German society, its attitudes toward the Jews and toward the anti-Jewish policy of the Nazi regime; as well as the Jewish society, its self-perception and its leadership